ILCOR Scientific Knowledge Gaps and Clinical Research Priorities for Cardiopulmonary Resuscitation and Emergency Cardiovascular Care: A Consensus Statement. Issue 22 (29th May 2018) - Kleinman, Monica E.; Perkins, Gavin D.; Bhanji, Farhan; Billi, John E.; Bray, Janet E.; Callaway, Clifton W.; de Caen, Allan; Finn, Judith C.; Hazinski, Mary Fran; Lim, Swee Han; Maconochie, Ian; Nadkarni, Vinay; et al.
Abstract : Despite significant advances in the field of resuscitation science, important knowledge gaps persist. Current guidelines for resuscitation are based on the International Liaison Committee on Resuscitation 2015 International Consensus on Cardiopulmonary Resuscitation and Emergency Cardiovascular Care Science With Treatment Recommendations, which includes treatment recommendations supported by the available evidence. The writing group developed this consensus statement with the goal of focusing future research by addressing the knowledge gaps identified during and after the 2015 International Liaison Committee on Resuscitation evidence evaluation process. Key publications since the 2015 International Consensus on Cardiopulmonary Resuscitation and Emergency Cardiovascular Care Science With Treatment Recommendations are referenced, along with known ongoing clinical trials that are likely to affect future guidelines.